ANALISIS KELAYAKAN USAHATANI CABAI RAWIT DI DESA KIRITANA KECAMATAN KAMBERA KABUPATEN SUMBA TIMUR - Pati, Susanti Rambu Koni; Wadu, Junaedin (Universitas Galuh, 2023)
ABSTRACT This study aims to analyze the income and feasibility of cayenne pepper farming in Kiritana Village, Kambera District, East Sumba Regency. The method of determining the research area was carried out by purposive sampling, which was determined deliberately, namely in Kiritana Village with the consideration that Kiritana Village is one of the areas with the majority of the population working as farmers, and cayenne pepper is one of the commodities that is generally cultivated in the village. The number of samples in this study were 69 sample farmers. This study uses income analysis and business feasibility (R/C ratio). The results of this study indicate that the average income of the sample farmers is IDR 18.721.967 / ha, and the farming is feasible for cultivation or development. The feasibility of farming is based on the calculation of the R/C ratio with a yield of 2.93, which means that each additional Rp. 1 in capital will increase income by Rp. 2.93.